2015
DOI: 10.1007/s10571-015-0227-1
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury-Induced Neuronal Apoptosis is Reduced Through Modulation of PI3K and Autophagy Pathways in Mouse by FTY720

Abstract: FTY720 is a synthetic compound produced by modification of metabolite from Isaria sinclairii. It is a novel type of immunosuppressive agent inhibiting lymphocyte egress from secondary lymphoid tissues, thereby causing peripheral lymphopenia. Growing evidences have suggested that apoptosis and autophagy were involved in the secondary brain injury after traumatic brain injury (TBI) although FTY720 exerted neuroprotective effects in a variety of neurological diseases except TBI. The present study was aimed to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 40 publications
(33 reference statements)
2
52
0
Order By: Relevance
“…The in vivo model of TBI employed in the present study was based on a weight-drop model described previously36. In brief, mice were anesthetized with chloral hydrate (1%, 5 ml/kg) intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo model of TBI employed in the present study was based on a weight-drop model described previously36. In brief, mice were anesthetized with chloral hydrate (1%, 5 ml/kg) intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…The scoring system was adapted from previously published methods39. A detailed description of our NSS testing procedure and the contribution of individual tasks to the composite NSS was published previously36. For grip test, mice were placed on a thin, horizontal, metal 45 cm long wire which was lay up between two vertical poles 45 cm above a foam pad.…”
Section: Methodsmentioning
confidence: 99%
“…Fingolimod reduces the accumulation of monocytes and IL-16 after TBI [20,21]. However, whether the administration of fingolimod can improve the functional outcome is still controversial [22,23]. A previous study demonstrated the reduction of neuroinflammation but no functional improvement with a single-dose administration of 1 mg/kg fingolimod before TBI [22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the 3-day therapy is chosen in this article. By reference to previous studies [21][22][23], the dose of 1 mg/kg is used in this study, which is approximately 10 times the FDA-approved dose of 0.5 mg/ day in humans on a milligram/square meter basis.…”
Section: Introductionmentioning
confidence: 99%
“…The model of TBI used in the present study was based on Marmarou's weight-drop model with some modifications as previously described by Flierl et al (Flierl et al, 2009; Zhang et al, 2016). Mice were anesthetized in a closed container on a wire mesh over ether-soaked cotton and then placed onto the platform directly under the weight of the weight-drop device.…”
Section: Methodsmentioning
confidence: 99%